2018
DOI: 10.1109/jproc.2018.2817118
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning in Compiler Optimization

Abstract: Abstract-In the last decade, machine learning based compilation has moved from an an obscure research niche to a mainstream activity. In this article, we describe the relationship between machine learning and compiler optimisation and introduce the main concepts of features, models, training and deployment. We then provide a comprehensive survey and provide a road map for the wide variety of different research areas. We conclude with a discussion on open issues in the area and potential research directions. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

5
4

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 196 publications
(264 reference statements)
0
103
0
Order By: Relevance
“…Energy and power optimization for embedded and mobile systems is an intensely studied field. There is a wide range of activities on exploiting compiler-based code optimization [12], [13], runtime task scheduling [14], [15], or a combination of both [7] to optimize different workloads for energy efficiency. Other relevant work in web browsing optimization exploits application knowledge to batch network communications [16], [17], and parallel downloading [18], which primarily target the initial page loading phase.…”
Section: A Energy Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy and power optimization for embedded and mobile systems is an intensely studied field. There is a wide range of activities on exploiting compiler-based code optimization [12], [13], runtime task scheduling [14], [15], or a combination of both [7] to optimize different workloads for energy efficiency. Other relevant work in web browsing optimization exploits application knowledge to batch network communications [16], [17], and parallel downloading [18], which primarily target the initial page loading phase.…”
Section: A Energy Optimizationmentioning
confidence: 99%
“…Specifically, PES employs an analytical model to choose the operating frequency of the processor to reduce energy consumption. Developing an effective analytical model requires deep knowledge of the underlying hardware and the application domains [7]. As a result, PES offers a poor hardware portability because tuning a model for a new hardware platform could involve significant overhead.…”
Section: Introductionmentioning
confidence: 99%
“…Our approach avoids the pitfall by automatically learning how to best schedule rendering process. There are also works use statistical modeling or control theories to optimize energy efficiency on mobiles [16], [17], [18], [19], [20], [21]. While not specific to web browsing, these studies demonstrate the advantages and needs for adaptive systemlevel optimizations.…”
Section: Related Workmentioning
confidence: 99%
“…Predictive Modeling. Recent studies have shown that machine learning based predictive modeling is effective in code optimization [43], [44], performance predicting [45], [46], parallelism mapping [20], [47], [48], [49], [50], and task scheduling [51], [52], [53], [54], [55], [56]. Its great advantage is its ability to adapt to the ever-changing platforms as it has no prior assumption about their behavior.…”
Section: Domain-specific Optimizationsmentioning
confidence: 99%